Pengaruh Model Kooperatif Tipe Make A Match Terhadap Hasil Belajar Siswa Kelas V SDN Sumbertanggul 2 Kabupaten Mojokerto - Utari, Febi Dinda; Fadlillah, M. (JOURNAL OF EDUCATION FOR ALL, 2024)
This research is quantitative research. The aim of this research is to determine the effect of implementing the make a match type cooperative learning model on students' learning outcomes in mathematics in multiplication material for class V SDN Sumbertanggul 2. The design of this research is one group pre-test post-test. The sample used in this research was class V students at SDN Sumbertanggul 2, totaling 25 students, 13 male students and 12 female students. The sampling technique used is saturated sampling. Data collection techniques in research include interviews, questionnaires, tests, documentation, teacher and student observations. The results of this research show that there is an influence from the application of the make a match type cooperative learning model on student learning outcomes in mathematics in multiplication material for class V at SDN Sumbertanggul 2, Mojokerto Regency. This is shown in the t count results obtained in the paired sample t - test, namely the t count has a negative value which indicates rejection of h0, with t count results of -27, 107 and t table 2.068, so  t count < - t table which means h0 is rejected and h1 is accepted. The significance value obtained is 0.00 < 0.05, so it can be concluded that there is an average difference between the pre-test and post-test results.